Rapid Analysis of Eukaryotic Bioluminescence to Assess Potential Groundwater Contamination Events - Zacariah L. Hildenbrand; Alexandra Osorio; Doug D. Carlton; Brian E. Fontenot; Jayme L. Walton; Laura R. Hunt; Hyppolite Oka; Dan Hopkins; Bryan Bjorndal; Kevin A. Schug (Journal of Chemistry)
Here we present data using a bioluminescent dinoflagellate, Pyrocystis lunula, in a toxicological bioassay to rapidly assess potential instances of groundwater contamination associated with natural gas extraction. P. lunula bioluminescence can be quantified using spectrophotometry as a measurement of organismal viability, with normal bioluminescent output declining with increasing concentration(s) of aqueous toxicants. Glutaraldehyde and hydrochloric acid (HCl), components used in hydraulic fracturing and shale acidization, triggered significant toxicological responses in as little as 4 h. Conversely, P. lunula was not affected by the presence of arsenic, selenium, barium, and strontium, naturally occurring heavy metal ions potentially associated with unconventional drilling activities. If exogenous compounds, such as glutaraldehyde and HCl, are thought to have been introduced into groundwater, quantification of P. lunula bioluminescence after exposure to water samples can serve as a cost-effective detection and risk assessment tool to rapidly assess the impact of putative contamination events attributed to unconventional drilling activity.